Research progress of auricular bean embedding in the treatment of chemotherapy-induced nausea and vomiting (耳穴埋豆缓解化疗所致恶心呕吐的研究进展) - YANG Ge (杨鸽); HUANG Junheng (黄俊衡); WANG Xiaoli (王小莉) (中西医结合护理)
Nausea and vomiting is one of the common adverse drug reactions associated with chemotherapy in cancer patients, and it has negative impact on following treatment and health-related quality of life. Traditional Chinese Medicine (TCM) external treatment plays an important role in the treatment of chemotherapy-induced nausea and vomiting, and has achieved good therapeutic effect in clinical application. Auricular bean embedding, as a common TCM external treatment technique, is accepted by patients because of its non-invasive and high safety. This article summarizes the relevant literature on the treatment of chemotherapy-induced nausea and vomiting with auricular bean embedding in recent years, so as to provide reference for clinical application. (恶心呕吐是化疗常见的不良反应之一, 严重影响患者的后续治疗和生活质量。中医外治法在治疗化疗所致恶心呕吐方面发挥了重要的作用。本研究就耳穴埋豆中医外治法缓解化疗所致恶心呕吐的研究现状进行综述, 旨在为临床制定中西医结合干预方案提供参考。)